Expulsion d’etrangers et Convention européenne des droits de l’homme Le risque de mauvais traitements dans l’Etat de destinatio (2010)
The right of States, for a variety of reasons, to expel aliens has never been disputed by the European Court of Human Rights insofar as a State party to the European Convention on Human Rights continues, quite naturally, to exercise its sovereignty over its territory. However, this right has to be reconciled with the obligation of States parties to the European Convention on Human Rights not to expose aliens and, more generally, persons under their jurisdiction to a risk of violation of the provisions of the Convention. Yet, guaranteeing that no human right recognized as such by the Convention be violated in case of expulsion is too heavy a task for States to assume. Imposing such an obligation would end up in invalidating the sovereign right of States to expel aliens. The Court of Strasbourg retains primarily the risk of Article 3 of the Convention being violated in expulsion cases, a provision according to which inhuman or degrading punishments or treatments and, of course, acts of torture are strictly prohibited. The Court’s case-law, abundant as well as rich in nuances, results in rather a thorough examination of the human rights situation in any country towards which a alien will be (or has already been) expelled.